EMPLOYER BRANDING AS A TOOL FOR EMPLOYEE LOYALTY: THE CASE OF MOROCCAN COMPANIES LISTED ON CASABLANCA STOCK EXCHANGE: Received: 24th April 2023; Revised: 27th July 2023, 11th August 2023; Accepted: 15th August 2023 - OUACHI, Soukayna; ALAOUI, Meriem (PEOPLE: International Journal of Social Sciences, 2023)
To attract qualified profiles, known as talents, and to retain them, many enterprises are actively leveraging on employer branding. The objective of this research is to shed light on the role played by the concept of employer branding, defined as the set of brand image assets with respect to employees and their impact on human resources loyalty. Our hypothetico-deductive research method will be completed by conducting an empirical study based on a series of semi-structured interviews with 10 large companies listed on Casablanca stock exchange market. We suggest a model to articulate the employer brand around three key dimensions: low propensity to seek a new job, affective engagement and task performance. The collected and analyzed feedback led us to a clear and obvious conclusion. The intention to leave the company, the affective commitment as well as the performance in the task are directly impacted by the attributes of the employer brand. Therefore, organizational loyalty is influenced by the employer brand. The latter is a powerful loyalty tool that allows the company to retain talent. Further research should be conducted to explore the potential of employer branding as a powerful tool for talent retention.